Creating virtual architectural education in a traditional environment: Prospects and challenges - Oluropo Stephen Ilesanmi; S. C. Folorunso; O. O. Kolade (ARTEKS : Jurnal Teknik Arsitektur, 2023)
The advent of computer technology has set off an information explosion that has changed civilization and indeed the entire workforce of today’s world. These changes presage a new context in which architecture schools must function. Traditionally, architectural education is basically between a group of persons; the teacher and the learner(s) in a defined classroom space. This mode of knowledge delivery makes the students to adopt a passive position (based on just listening to the teacher). This prevents the diversity of ideas, promotes repetitive learning and kills creativity. Virtual education on the other hand refers to instruction in a learning environment where teacher and student are separated by time or space, or both. In this knowledge delivery mode, students’ take responsibility of their learning process in an active way. Multimedia tools, electronic media like a discussion forum, chat room, voice mail, and e-mail are employed for communication. The benefits inherent in this type of learning process include sharing of resources and learning environment, promotion of collaborative learning, effective education delivery and educational programme enhancement. In this paper, the concept “virtual architectural education” is considered together with the inherent benefits for the architecture schools and profession.